2019
DOI: 10.1007/s10637-018-00721-z
|View full text |Cite
|
Sign up to set email alerts
|

LEF1-AS1 contributes to proliferation and invasion through regulating miR-544a/ FOXP1 axis in lung cancer

Abstract: SummaryLong non-coding RNAs (lncRNAs) are increasingly recognized as important regulators in tumor development. This study aims to investigate the potential role oflncRNALEF1-AS1, in the progression of lung cancer. Quantitative real-time PCR (qRT-PCR) and western blot assays showed that LEF1-AS1 was upregulated while miR-544a was downregulated in lung cancer specimens and cells. Overexpression of LEF1-AS1 led to the enhancement of cell proliferation and invasion, revealed by CCK-8 assay and transwell assay. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…Lymphoid enhancer-binding factor 1 (LEF1) antisense RNA 1 (LEF1-AS1), is a highly conserved transcript and a newfound lncRNA encode in the plus strand of LEF1 at chromosome 4q25, which is rstly found to be upregulated and predict prognosis in CRC [6]. In recent years, the distinct upregulation of LEF1-AS1 was demonstrated in several tumors, such as glioblastoma, oral squamous cell carcinoma, lung cancer and prostate cancer [7][8][9][10]. However, LEF1-AS1 is highly expressed in normal hematopoietic stem cells but barely detectable in myeloid malignant cell lines [11].…”
Section: Introductionmentioning
confidence: 99%
“…Lymphoid enhancer-binding factor 1 (LEF1) antisense RNA 1 (LEF1-AS1), is a highly conserved transcript and a newfound lncRNA encode in the plus strand of LEF1 at chromosome 4q25, which is rstly found to be upregulated and predict prognosis in CRC [6]. In recent years, the distinct upregulation of LEF1-AS1 was demonstrated in several tumors, such as glioblastoma, oral squamous cell carcinoma, lung cancer and prostate cancer [7][8][9][10]. However, LEF1-AS1 is highly expressed in normal hematopoietic stem cells but barely detectable in myeloid malignant cell lines [11].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs influence posttranscriptional regulation in various genes, and some have been shown to influence osteoporosis[20,21]. MiR-544a has been shown to play an important role in many diseases such as lung cancer and breast cancer, but its role in osteoporosis is unknown[22,23]. Here, we showed that miR-544a suppressed osteogenesis and promoted osteoclastogenesis by downregulating the expressions of RUNX2 , Osterix , ALP, Col1a1 , OPN , OCN and OPG .…”
Section: Discussionmentioning
confidence: 69%
“…15 Furthermore, it was demonstrated that LEF1-AS1 regulates growth and migration of lung cancer cells by sponging miR-544a and enhancing FOXP1 translation. 26 LEF1-AS1 was also demonstrated to regulate proliferation and metastasis of oral squamous cell carcinoma and myeloid tumor. 16,27 Thus, LEF1-AS1 is a very important lncRNA involved in tumorigenesis.…”
Section: Discussionmentioning
confidence: 97%
“…13 A number of experiments have confirmed that LEF1-AS1 is a sponge for several miRNAs, including miR-330-5p, miR-544a and miR-489. 15,17,26 LncRNA could directly interact with miRNAs to suppress their levels, consequently inducing upregulation of the miRNA downstream genes. 29 For instance, LINC01116 interacts with miR-136 to promote FN1 expression in oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%